1995
DOI: 10.1128/iai.63.9.3582-3586.1995
|View full text |Cite
|
Sign up to set email alerts
|

Enteral human serum immunoglobulin treatment of cryptosporidiosis in mice with severe combined immunodeficiency

Abstract: The anti-cryptosporidial immunoglobulin G antibodies in two commercially available human serum immunoglobulin (HSIG) products were quantified and characterized. The mean level of Cryptosporidium parvum-specific immunoglobulin G in HSIG was eightfold higher than the antibody level found in the sera of three immunocompetent individuals convalescing from cryptosporidiosis. However, HSIG products displayed no reactivity to cryptosporidial antigens in immunoblot analyses, while convalescent-phase sera demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A few case reports have suggested that hyperimmune bovine colostrum may modify the disease course of Cryptosporidium infection in immunocompromised hosts (38, 39). Other therapies include passive immunization via human breast milk or oral human immunoglobulin (40–42). However, these have been studied only in observational studies or in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have suggested that hyperimmune bovine colostrum may modify the disease course of Cryptosporidium infection in immunocompromised hosts (38, 39). Other therapies include passive immunization via human breast milk or oral human immunoglobulin (40–42). However, these have been studied only in observational studies or in vitro assays.…”
Section: Discussionmentioning
confidence: 99%